Production of biodiesel from Palm Fatty Acid Distillate: kinetic study / Amril Syafiq, Wan Zuraida Wan Kamis, Nur Alwani Ali Bashah and Fakhrony Sholahudin - Syafiq, Amril; Wan Kamis, Wan Zuraida; Ali Bashah, Nur Alwani; Sholahudin, Fakhrony (2020)
As the fossil fuels are depleting and eventually will be gone forever, the studies and research have been conducted to find the alternative for the fossil fuels. The most suitable alternative for fossil fuels are biodiesel. Biodiesel or known as fatty acid methyl esters (FAME) usually obtained from green resources such as plant oil, animal fats or even waste cooking oils. Next, Palm Fatty Acid Distillate (PFAD) which is by-product of Palm Oil will be used as the main material as it contains high concentration of free fatty acid (FFA). In this study, a mathematical kinetic model of esterification will develop by using a software named MATLAB. Rate constant will also be determined by the end of this study by using rate law. Rate of reaction or known as rate constant (k) is vital in process because it will determine the time taken for the process to complete. From the rate constant for both forward and backward reaction obtained, values of activation energy and the pre-exponential factor values for both reactions at can be determined with plotting Arrhenius plot. A general kinetic model and parametric study of the kinetics of the reaction involved in the production of biodiesel developed in this project through use of MATLAB Sequential Quadratic Programming and ODE45 have shown promising results. The objective of this project is achieved.